Hungarian Monitoring, 1 October 1990 . [Magyar rádiófigyelő], 1990. október 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Opposition demonstration in Kiev - Baltic countries' information agency in Denmark - German Christian Democratic Union's unification congress - Soviet parliament's law on conscience Domestic Affairs: - Local authority election results - Lack of interest in elections - Announcement of new election round - József Antall in Hamburg - Géza Jeszenszky at the Warsaw Pact foreign ministers' meeting - European Food and Nutrition Policy Conference in Budapest - Vojvodina Forum set up Economy: - High inflation, rising food prices - Fee reductions, introducing taxes - Motorway funded by Israeli and Italian capital Külpolitika: - Ellenzéki tüntetés Kijevben - A balti országok információs képviselete Dániában - A CDU egyesülési kongresszusa - A szovjet parlament lelkiismereti törvénye Belpolitika: - A helyhatósági választások eredményei - Választási érdektelenség - Új választási forduló kiírása - Antall József Hamburgban - Jeszenszky Géza a Varsói Szerződés külügyminiszteri értekezletén - Európai Élelmezési és Táplálkozáspolitikai Konferencia Budapesten - Vajdasági Fórum megalakulása Gazdaság: - Magas infláció, növekvő élelmiszerárak - Illetékcsökkentés, adóbevezetés - Autópálya izraeli és olasz tőkével